2002
DOI: 10.1053/jhep.2002.30277
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl transpeptidase overexpression increases metastatic growth of B16 melanoma cells in the mouse liver

Abstract: B16 melanoma (B16M) cells with high glutathione (GSH) content show rapid proliferation in vitro and high metastatic activity in the liver in vivo. ␥-Glutamyl transpeptidase (GGT)-mediated extracellular GSH cleavage and intracellular GSH synthesis were studied in vitro in B16M cells with high (F10) and low (F1) metastatic potential. GGT activity was modified by transfection with the human GGT gene (B16MF1/Tet-GGT cells) or by acivicin-induced inhibition. B16MF1/Tet-GGT and B16MF10 cells exhibited higher GSH con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
86
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 47 publications
8
86
0
Order By: Relevance
“…Hence, GGT expression provides tumor cells with a growth advantage at physiologic concentrations of cyst(e)ine (14). Consequently, we found that tumor GGT activity and an intertissue flow of GSH, where the liver plays a key role, regulate GSH content of B16 melanoma cells and thereby their metastatic growth (15).…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Hence, GGT expression provides tumor cells with a growth advantage at physiologic concentrations of cyst(e)ine (14). Consequently, we found that tumor GGT activity and an intertissue flow of GSH, where the liver plays a key role, regulate GSH content of B16 melanoma cells and thereby their metastatic growth (15).…”
mentioning
confidence: 79%
“…Culture of B16-F10 Melanoma Cells-Murine B16-F10 melanoma cells (from the ATCC, Manassas, VA) were cultured in serum-free Dulbecco's modified Eagle's medium (DMEM; Invitrogen), pH 7.4, supplemented with 10 mM HEPES, 40 mM NaHCO 3 , 100 units/ml penicillin, and 100 g/ml streptomycin (15). Cells were harvested by incubation for 5 min with 0.05% (w/v) trypsin (Sigma) in PBS (10 mM sodium phosphate, 4 mM KCl, 137 mM NaCl), pH 7.4, containing 0.3 mM EDTA, followed by the addition of 10% calf serum to inactivate the trypsin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations